KEPASTIAN HUKUM PERJANJIAN YANG MENCANTUMKAN KLAUSULA ARBITRASE BERDASARKAN PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) DI PENGADILAN NIAGA - Sugiarto, Toharta; Hakim, Nur; TW, Gatut Hendro (SINERGI : Jurnal Riset Ilmiah, 2025)
Article 3 of Law Number 30 of 1999 states that the District Court has no authority to adjudicate disputes between parties who are bound by an arbitration agreement, while Article 303 of UUK PKPU states that the Commercial Court remains authorized to examine and resolve applications for bankruptcy declarations from parties bound by agreements that contain clauses arbitration, as long as the debt that is the basis for the application for a bankruptcy declaration meets the provisions as intended in Article 2 paragraph (1) of the KPKPU Law. This of course gives rise to differences in interpretation and law enforcement in resolving business disputes that include arbitration clauses. The formulation in this research is what is the process for resolving dispute agreements that include an agreed arbitration clause based on the provisions of Law Number 30 of 1999 concerning arbitration and dispute resolution? And how is the legal certainty that agreements containing arbitration clauses will be judged based on requests for postponement of debt payment obligations (PKPU) in the Commercial Court? Legal Certainty Theory according to Gustav Radbruch and Agreement Theory according to Mariam Darus Badrulzaman. The method used in this research is normative juridical research in the form of library legal materials or secondary data with primary, secondary and tertiary sources of legal materials. The research approach used is statutory, conceptual, analytical and case approaches as well as techniques for collecting legal materials by identifying and inventorying positive legal rules, book literature, journals and other sources of legal materials. The analysis technique for legal materials is carried out using systematic and grammatical interpretation as well as analogical construction. The results of the research show that the process of resolving dispute agreements that include arbitration clauses that are agreed upon based on the provisions of Law Number 30 of 1999 concerning arbitration and dispute resolution is a legal dualism, where the dispute resolution process can be resolved according to arbitration procedures as long as the cooperation agreement is agreed upon by the parties. made in writing and includes an arbitration clause. However, when one of the parties to a dispute submits a PKPU application, the Commercial Court still has the authority to examine and decide the case even if the agreement contains an arbitration clause provided that the application submitted meets the requirements stated in Article 222 of the PKPU UUK. The legal certainty of an agreement containing an Arbitration clause is judged based on a request for postponement of debt payment obligations (PKPU) in the Commercial Court, namely that it remains legally valid and binding for the parties even though a PKPU Application is being submitted to the debtor, because basically this issue only refers to default in terms of debt payment , for this reason, anyone has the right to submit a PKPU debtor application so that when the Commercial Court declares PKPU, the creditor will no longer suffer losses due to debts that are not paid by the Debtor